Perancangan Kampanye “Embracing Your Beauty: A Journey Of Self-Love” “Omg” Beauty Class di Cirebon - Angelika Angelika; Ine Rachmawati; Yuni Awalaturrohmah Solihah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Research aims to explore the perceptions of women aged 21-38 years old on self-confidence, feelings of insecurity, and self-love through an online survey conducted using Google Forms. The survey results show that 98.4% of respondents experience feelings of insecurity, while 75.8% show interest in attending self-development activities such as beauty classes to enhance self-confidence, and 91.3% show interest in makeup. Interviews were conducted to gain a deeper understanding of the beauty class activities conducted by OMG Beauty in Cirebon, which focus on developing makeup skills and using beauty products, but the interviews also revealed that these activities do not fully reflect OMG Beauty's brand image, which promotes the message